A Sb(SeO3)(HSeO3) crystal form, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611459204.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-19
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的之一在于提供一种Sb(SeO3)(HSeO3)晶体形式,以解决现有光学介质阻碍了光电系统小型化的问题
本发明中的Sb(SeO3)(HSeO3)晶体在波长546nm处的理论计算双折射率为0.350,在实现相同相位延迟效果时,所需晶体厚度更小,便于光学器件向微型化方向发展。
Smart Images

Figure CN122980032A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of crystal materials technology, specifically to a Sb(SeO3)(HSeO3) crystal form, its preparation method, and its application. Background Technology
[0002] In various linear and nonlinear optical devices, advanced optical communication networks, and fiber optic sensors, birefringent materials play a fundamental role due to their excellent polarization modulation performance. As the core carrier of various polarization devices, the working principle of birefringent crystals stems from their inherent optical anisotropy.
[0003] Existing optical media suffer from problems such as difficulty in removing impurities (e.g., natural mineral resources MgF2 and CaCO3), strong absorption characteristics below 400nm (opaqueness) which limit their application to the near-infrared band (e.g., YVO4 crystal), and low birefringence (e.g., α-BaB2O4 crystal), which hinder the miniaturization of optoelectronic systems. Summary of the Invention
[0004] One of the objectives of this invention is to provide a Sb(SeO3)(HSeO3) crystal form to solve the problem that existing optical media hinder the miniaturization of optoelectronic systems.
[0005] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: A Sb(SeO3)(HSeO3) crystal form, wherein the Sb(SeO3)(HSeO3) crystal is a crystal with a centrosymmetric structure; Using Cu-Kα radiation, the PXRD pattern of the Sb(SeO3)(HSeO3) crystal includes characteristic diffraction peaks at 2θ values of 6.06°, 12.10°, 25.52°, 27.42°, 31.92°, 36.92°, 43.22°, 44.84°, 54.32°, 54.78°, 56.52°, and 67.38°, with an error of ±0.2° for the 2θ values.
[0006] Furthermore, the crystal is orthorhombic, the space group is Cmce, and the cell parameters are: a(Å)=5.5791(3), b(Å)=6.9739(3), c(Å)=29.2383(17), α(°)=90°, β(°)=90°, γ(°)=90°, and the cell volume (Å) is... 3 The value is 1137.61(10), and the number of units in the formula is 8.
[0007] Furthermore, the crystal is formed as a single crystal, the space group is Cmce, and the cell parameters are: a(Å)=5.5791(3), b(Å)=6.9739(3), c(Å)=29.2383(17), and the cell volume (Å) is... 3 The value is 1137.61(10), and the number of units in the formula is 8.
[0008] Furthermore, using Cu-Kα radiation, the crystal exhibits the strongest characteristic diffraction peak at 2θ = 27.42° with a relative intensity of 100%, where the error in the 2θ value is ±0.20°.
[0009] Furthermore, the crystal has a theoretically calculated birefringence of 0.350 at a wavelength of 546 nm, and an experimentally measured ultraviolet absorption edge of 309 nm.
[0010] A second objective of this invention is to provide a method for preparing Sb(SeO3)(HSeO3) crystals, comprising: After the reaction raw materials are dissolved in the solvent, an acidic liquid is added to adjust the pH of the reaction system to 0.5±0.3. After static growth reaction, Sb(SeO3)(HSeO3) crystals are obtained. The reaction raw materials include soluble selenium-containing compounds and soluble antimony-containing compounds; The solvent includes deionized water.
[0011] Furthermore, the molar ratio of the soluble selenium-containing compound to the soluble antimony-containing compound is 1.8~2.2:1; The soluble selenium-containing compound includes selenium dioxide, and the soluble antimony-containing compound includes antimony trifluoride; The conditions for the static growth reaction include: reaction at room temperature for 7 to 15 days; The acidic liquid includes 80% sulfuric acid.
[0012] A third objective of this invention is to provide a polarizer made of the Sb(SeO3)(HSeO3) crystal described in one objective, or... It is made from Sb(SeO3)(HSeO3) crystals obtained by the preparation method described in Objective 2.
[0013] A fourth objective of this invention is to provide a phase retardation sheet made of the Sb(SeO3)(HSeO3) crystal described in one objective, or... It is made from Sb(SeO3)(HSeO3) crystals obtained by the preparation method described in Objective 2.
[0014] The fifth objective of this invention is to provide a polarization beam splitter element made of the Sb(SeO3)(HSeO3) crystal described in the first objective, or... It is made from Sb(SeO3)(HSeO3) crystals obtained by the preparation method described in Objective 2.
[0015] Beneficial effects: The Sb(SeO3)(HSeO3) crystal in this invention has a theoretically calculated birefringence of 0.350 at a wavelength of 546 nm. To achieve the same phase delay effect, a smaller crystal thickness is required, which facilitates the miniaturization of optical devices. Attached Figure Description
[0016] Figure 1 This is a diagram illustrating the birefringence of calcite crystals. Figure 2 A schematic diagram of Sb(SeO3)(HSeO3) crystals used in polarizers; Figure 3 Sb(SeO) 3) PXRD pattern of (HSeO3) crystal measured in practice; Figure 4 The figure shows a comparison between the measured PXRD patterns of Sb(SeO3)(HSeO3) crystals and the theoretically simulated PXRD patterns. Figure 5 The theoretically calculated band structure diagram of Sb(SeO3)(HSeO3) crystal; Figure 6 The graph shows the refractive index and birefringence properties of Sb(SeO3)(HSeO3) crystals. Figure 7 The image shows the UV-Vis diffuse reflectance spectrum of Sb(SeO3)(HSeO3) crystal. Figure 8 Figure 1 shows a schematic diagram of the crystal structure of Sb(SeO3)(HSeO3), where (a) is a schematic diagram of the three-dimensional structure of the crystal and (b) is a schematic diagram of the cross-section of the crystal along plane ab. Detailed Implementation
[0017] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention.
[0018] In various linear and nonlinear optical devices, advanced optical communication networks, and fiber optic sensors, birefringent materials play a fundamental role due to their excellent polarization modulation performance. As the core carrier of various polarization devices, the working principle of birefringent crystals stems from their inherent optical anisotropy. Specifically, when light waves enter the surface of such crystals, birefringence occurs, splitting the light into two beams with different characteristics: one is the "o-ray" (ordinary ray) with a fixed refractive index and following the law of refraction; the other is the "e-ray" (extra-ray) with a refractive index that changes with the propagation path and does not follow the conventional law of refraction. Due to the difference in propagation speed and direction, the two beams will produce a specific spatial angle, the magnitude of which is determined by the polarization state of the light waves and the incident direction. Taking birefringent crystal calcite as an example... Figure 1 As shown, when unpolarized incident light enters a calcite crystal, it is decomposed into two linearly polarized beams with different propagation directions due to the anisotropy of the crystal: the ordinary ray (o-ray) and the extraordinary ray (e-ray); among which... Figure 1 The dashed line in the image represents the optical axis of the calcite crystal. The o-ray follows the ordinary law of refraction, while the e-ray is deflected, visually demonstrating the physical effect of birefringence.
[0019] Birefringent crystals function optically similarly to a pair of polarizers with orthogonal transmission axes. In practical applications, they are the cornerstone of devices such as phase-matching elements, optical waveplates, beam splitters, circulators, and polarizers. Throughout the development of this field, researchers have successfully synthesized various birefringent crystal series, including LiNbO3, TiO2, MgF2, CaCO3, YVO4, and α-BBO. Among these, α-BBO, YVO4, and industrial calcite have become dominant in commercial polarization and compensation devices.
[0020] Although the aforementioned crystals are widely used, they still face limitations in terms of overall optical performance and applicable wavelength range. To meet the ever-evolving demands of optical devices, academia and industry are currently dedicated to developing novel crystal materials with higher birefringence, especially large birefringent crystals with excellent performance in the ultraviolet spectral region. This is also one of the core demands of current materials research and development.
[0021] Among known optical media, different materials often face specific limitations in their technical applications. Take the structurally simple binary halide MgF2 as an example; its core advantage lies in its extremely wide transparency window (130nm to 8μm), thus dominating the deep ultraviolet birefringent materials market. However, its low birefringence (0.012@546nm) significantly reduces its practical value. While the most widely used commercially available CaCO3 crystal can cover the visible to part of the ultraviolet spectral region, as a natural mineral resource, its intrinsic impurities are difficult to remove, making it extremely difficult to meet the stringent requirements for material yield and quality in high-precision optical polarizing prisms.
[0022] Furthermore, while artificially synthesized YVO4 crystals exhibit excellent birefringence (up to 0.216@532nm), their strong absorption characteristics below 400nm (opaqueness) limit their applications to the near-infrared band. Even though α-BaB₂O₄ crystals perform well in overall optical properties, their birefringence is still inferior to materials like YVO₄ and rutile. This characteristic necessitates a larger crystal thickness for polarization device design, hindering the miniaturization of optoelectronic systems.
[0023] Therefore, designing and synthesizing a novel ultraviolet birefringent crystal that combines wide ultraviolet transmittance and strong optical anisotropy to meet the needs of the next generation of optoelectronic industry for micro optical components has become the key to breaking the deadlock.
[0024] Based on this, one object of the present invention is to provide a Sb(SeO3)(HSeO3) crystal form, wherein the Sb(SeO3)(HSeO3) crystal is a crystal with a centrosymmetric structure; using Cu-Kα radiation, the PXRD pattern (X-ray powder diffraction pattern) of the Sb(SeO3)(HSeO3) crystal includes characteristic diffraction peaks at 2θ (diffraction angles) of 6.06°, 12.10°, 25.52°, 27.42°, 31.92°, 36.92°, 43.22°, 44.84°, 54.32°, 54.78°, 56.52°, and 67.38°, wherein the error of the 2θ value is ±0.2°.
[0025] The Sb(SeO3)(HSeO3) crystal in this invention is based on the design principles of microscopic crystal structures, introducing trigonal pyramidal anionic functional groups [SeO3]. 2- Selenite and [HSeO3] - The hydrogen selenite ion serves as the core functional group of the crystal; simultaneously utilizing the central Se... 4+ The high asymmetry brought about by the stereoactive lone pair electrons of the ion, combined with Sb which also has lone pair electrons, 3+ Ions are used to construct building blocks with extremely strong intrinsic optical anisotropy. These microscopic units are then guided to align cooperatively in the crystal lattice to form a low-dimensional topological structure. Subsequent testing revealed that the crystal in this invention has a theoretically calculated birefringence of approximately 0.350 at a wavelength of 546 nm and an ultraviolet absorption edge of 309 nm. This demonstrates that the crystal in this invention is a novel ultraviolet birefringent crystal that combines wide ultraviolet transmittance with strong optical anisotropy.
[0026] Furthermore, the structural diagram of the Sb(SeO3)(HSeO3) crystal in this invention is shown below. Figure 8As shown, in the Sb(SeO3)(HSeO3) crystal, Sb atoms coordinate with oxygen atoms to form [SbO5] polyhedra; Se atoms exist in two coordination environments, namely selenite [SeO3]. 2- Trigonal pyramidal group and hydroselenoate [HSeO3] - Trigonal pyramidal group; [SbO5] polyhedron, [SeO3] 2- Triangular pyramid, [HSeO3] - Trigonal pyramids are interconnected through shared-vertex oxygen atoms, forming the framework of the two-dimensional layered structure of Sb(SeO3)(HSeO3) crystal in this invention; furthermore, OH...O hydrogen bonding exists within the crystal structure (see appendix). Figure 8 (not shown in the image), further stabilizing the overall crystal framework.
[0027] In some embodiments, Cu-Kα radiation is used, and the PXRD pattern expressed at a 2θ angle includes peaks at the following diffraction angles (2θ) (as shown in Table 1): Table 1.
[0028] In some embodiments, Cu-Kα radiation is used, and the crystal exhibits the strongest characteristic diffraction peak at 2θ = 27.42° with a relative intensity of 100%, wherein the error of the 2θ value is ±0.20°.
[0029] In some embodiments, Cu-Kα radiation is used, and the PXRD pattern expressed at a 2θ angle includes peaks at the following diffraction angles (2θ) (as shown in Table 2): Table 2.
[0030] In some embodiments, the crystal is an orthorhombic crystal system, the space group is Cmce, and the cell parameters are: a(Å)=5.5791(3), b(Å)=6.9739(3), c(Å)=29.2383(17), α(°)=90°, β(°)=90°, γ(°)=90°, and the cell volume (Å) is... 3 The value is 1137.61(10), and the number of units in the formula is 8.
[0031] In some embodiments, the crystal is formed as a single crystal, the space group is Cmce, and the cell parameters are: a(Å)=5.5791(3), b(Å)=6.9739(3), c(Å)=29.2383(17), and the cell volume (Å) is... 3 The value is 1137.61(10), and the number of units in the formula is 8.
[0032] In some embodiments, the crystal has a theoretically calculated birefringence of 0.350 at a wavelength of 546 nm, and an experimentally measured ultraviolet absorption edge of 309 nm.
[0033] One object of the present invention is to provide a method for preparing Sb(SeO3)(HSeO3) crystals, comprising: After the reaction raw materials are dissolved in the solvent, an acidic liquid is added to adjust the pH of the reaction system to 0.5±0.3. After static growth reaction, Sb(SeO3)(HSeO3) crystals are obtained. The reaction raw materials include soluble selenium-containing compounds and soluble antimony-containing compounds; The solvent includes deionized water.
[0034] In some embodiments, the molar ratio of the soluble selenium-containing compound to the soluble antimony-containing compound is 1.8 to 2.2:1; The soluble selenium-containing compound includes selenium dioxide, and the soluble antimony-containing compound includes antimony trifluoride; The conditions for the static growth reaction include: reaction at room temperature for 7 to 15 days; The acidic liquid includes 80% sulfuric acid (i.e., sulfuric acid with a mass fraction of 80%).
[0035] The preparation method of Sb(SeO3)(HSeO3) crystal in this invention has the following characteristics: (1) Mild operating conditions: The static growth reaction is completed at normal pressure and room temperature. No high-temperature hydrothermal or solvothermal high-pressure reactor is required during the preparation process, which has the characteristics of simple process and easy operation. Furthermore, the room temperature of the static growth reaction is preferably 23~32°C.
[0036] (2) Controllable crystal growth rate: The crystal preparation in this invention adopts a static growth reaction, which mainly involves slow evaporation of the solvent to crystallize, which is conducive to obtaining block crystals with high crystal quality, few defects and complete morphology, and improves the optical performance of the crystal to a certain extent.
[0037] (3) High crystal purity: Subsequent testing revealed that the characteristic diffraction peaks in the measured PXRD pattern of the crystal obtained in this invention are completely consistent with the characteristic diffraction peaks in the PXRD pattern simulated by computer theory. This indicates that the Sb(SeO3)(HSeO3) crystal obtained in this invention contains no other crystalline phases and has high purity. Based on the above characteristics, the preparation method in this application has the feature of good synthesis repeatability and can stably reproduce the synthesis of the crystal.
[0038] Furthermore, the reactants in this invention are selected from soluble selenium-containing compounds and soluble antimony-containing compounds, enabling the preparation of a homogeneous reaction mother liquor. Crystallization is achieved through a static growth reaction (i.e., solvent evaporation method, relying on the slow evaporation of the solvent to crystallize at room temperature and pressure), avoiding the risk of high-temperature decomposition. The slow, orderly growth of the crystal, achieved through the homogeneous mother liquor, yields high-quality bulk single crystals with few defects, suitable for optical testing. The molar ratio of the soluble selenium-containing compound to the soluble antimony-containing compound is 1.8~2.2:1. Controlling the molar ratio of selenium to antimony in the reaction system within a predetermined range ensures a proper match between the crystal nucleation rate and the crystal growth rate, facilitating the acquisition of Sb(SeO3)(HSeO3) crystals with high crystal integrity. Moreover, this molar ratio also promotes the generation and orderly arrangement of the target crystal structural units, reducing the formation of impurity phases and ensuring that the product is a pure-phase Sb(SeO3)(HSeO3) crystal, resulting in a crystal material with a theoretically calculated birefringence of 0.350 at a wavelength of 546 nm and an ultraviolet absorption edge of 309 nm.
[0039] The 80% sulfuric acid used in this invention can provide sufficient hydrogen ions at room temperature to inhibit antimony ion hydrolysis and regulate the dissociation of selenite, so that the reaction system simultaneously contains the SeO3 required for crystal formation. 2- and HSeO 3- Meanwhile, its room temperature oxidizing power is relatively weak, and it can stably maintain Se. 4+ In terms of valence state, sulfate, as an obscured anion, does not participate in the crystal framework construction, thus ensuring the formation of pure-phase Sb(SeO3)(HSeO3) crystals to a certain extent. Furthermore, it can moderately slow down solvent evaporation, preventing explosive nucleation and facilitating the growth of high-quality bulk single crystals.
[0040] Furthermore, in practice, the Sb(SeO3)(HSeO3) crystals precipitated from the static reaction need to be washed multiple times with anhydrous ethanol or deionized water to remove residual mother liquor from the crystal surface, and then dried before subsequent testing and application.
[0041] One object of the present invention is to provide the polarizer said therein, which is made of Sb(SeO3)(HSeO3) crystal as described in one object, or made of Sb(SeO3)(HSeO3) crystal prepared in another object.
[0042] And a schematic diagram of the crystal used in a polarizer is shown below. Figure 2 As shown, from Figure 2 As can be seen, after the unpolarized incident light passes through the polarizing prism, it is split by the crystal birefringence effect in this invention, resulting in two linearly polarized beams with mutually perpendicular vibration directions; wherein, Figure 2In the diagram, 1 represents unpolarized incident light, 2 represents the entire polarizer, 3 represents the bonding interface between two Sb(SeO3)(HSeO3) crystals that have undergone post-processing and optical finishing to prepare the prism, 4 represents the first linearly polarized light, and 5 represents the second linearly polarized light.
[0043] One object of the present invention is to provide a phase delay film made of Sb(SeO3)(HSeO3) crystal as described in one object, or made of Sb(SeO3)(HSeO3) crystal prepared in another object.
[0044] One object of the present invention is to provide a polarization beam splitter made of Sb(SeO3)(HSeO3) crystal as described in one object, or Sb(SeO3)(HSeO3) crystal prepared as described in another object.
[0045] In addition to the above, the Sb(SeO3)(HSeO3) crystal in this invention can also be used to make phase modulation elements. Of course, in practice, the application of the Sb(SeO3)(HSeO3) crystal in this invention is not limited to what is described above.
[0046] In practice, the polarizer in this invention can be further assembled into a polarizing beam splitter, an optical isolator, an optical switch, and a polarization analysis device. It can also be used in visible and near-ultraviolet optical systems such as spectroscopic equipment and laser optical systems.
[0047] Example
[0048] The technical concept of the present invention will be further explained below through specific embodiments.
[0049] Example 1
[0050] A method for preparing Sb(SeO3)(HSeO3) crystals, comprising: Selenium dioxide and antimony trifluoride (with a molar ratio of 1.8:1) were dissolved in deionized water. 80% H2SO4 was added to adjust the acidity of the reaction system, keeping the pH within the range of 0.5±0.3. After filtration to remove undissolved substances, the system was allowed to stand for growth until pink transparent single crystals (i.e., Sb(SeO3)(HSeO3) crystals) precipitated. The obtained crystals were then separated and the residual mother liquor on the crystal surface was washed multiple times with anhydrous ethanol and dried. The conditions for the stand for growth were: 7 days at room temperature (32℃).
[0051] Example 2
[0052] A method for preparing Sb(SeO3)(HSeO3) crystals, comprising: Selenium dioxide and antimony trifluoride (with a molar ratio of 2:1) were dissolved in deionized water. 80% H2SO4 was added to adjust the acidity of the reaction system, keeping the pH within the range of 0.5±0.3. After filtration to remove undissolved substances, the system was allowed to stand for growth until pink transparent single crystals (i.e., Sb(SeO3)(HSeO3) crystals) precipitated. The obtained crystals were then separated and the residual mother liquor on the crystal surface was washed multiple times with anhydrous ethanol and dried. The conditions for the stand for growth were: 15 days at room temperature (23℃).
[0053] Example 3
[0054] Selenium dioxide and antimony trifluoride (with a molar ratio of 2.2:1) were dissolved in deionized water. 80% H2SO4 was added to adjust the acidity of the reaction system, keeping the pH within the range of 0.5±0.3. After filtration to remove undissolved substances, the system was allowed to stand for growth until pink transparent single crystals (i.e., Sb(SeO3)(HSeO3) crystals) precipitated. The obtained crystals were then separated and the residual mother liquor on the crystal surface was washed multiple times with anhydrous ethanol and dried. The conditions for the stand for growth were: 12 days at room temperature (25℃).
[0055] Test Analysis: 1. Single-crystal X-ray diffraction tests were performed on the Sb(SeO3)(HSeO3) single-crystal samples prepared in Example 2 under an optical microscope. The tests were conducted using a Rigaku XtaLAB SynergyR single-crystal diffractometer at 293(2) K, with Mo Kα radiation (λ=0.71073Å) and single-crystal X-ray diffraction data acquired in ω-scan mode. The initial crystal structure was determined using the SHELXT program, which is based on F... 2 The crystal structure of Sb(SeO3)(HSeO3) was refined using the full matrix least squares method, with anisotropic refinement applied to all non-hydrogen atoms and a geometric riding model used for hydrogen atoms. The determined space group and symmetry were further verified using the PLATON program to confirm the crystal structure and related crystallographic parameters. Crystal structure data are detailed in Table 3.
[0056] Table 3. Crystal structure data
[0057] As can be seen from Table 3, the Sb(SeO3)(HSeO3) crystal in this invention belongs to the orthorhombic crystal system with space group Cmce. This space group contains the crystallographic inversion symmetry center, directly proving from the perspective of crystal structure that the crystal described in this invention has a centrosymmetric structure.
[0058] 2. Powder X-ray diffraction (PXRD) tests were performed on the Sb(SeO3)(HSeO3) crystal obtained in Example 2 using a Shimadzu XRD-6100 powder X-ray diffractometer. The tests were conducted at room temperature, using Cu Kα as the radiation source, with a wavelength λ = 1.5418 Å, a 2θ scan range of 5–70°, and a scan rate of 7°·min. -1 For detailed test results, please see [link / reference]. Figure 3 .
[0059] Using Mercury software, theoretical diffraction patterns were simulated based on measured diffraction data from a single crystal. The simulation conditions were a Cu Kα target, wavelength of 1.5418 Å, and a 2θ range of 5–70°. The measured PXRD patterns of Sb(SeO3)(HSeO3) crystals were compared with the theoretically simulated PXRD patterns. Details can be found in [link to relevant documentation]. Figure 4 .
[0060] from Figure 3 It can be seen that, Figure 3 The positions of the diffraction peaks are basically the same as those in Table 2, indicating that the present invention has successfully obtained Sb(SeO3)(HSeO3) crystals.
[0061] from Figure 4 As can be seen, the positions of the diffraction peaks in the measured PXRD pattern of Sb(SeO3)(HSeO3) crystal are completely consistent with the positions of the diffraction peaks in the theoretically simulated PXRD pattern. This shows that the measured diffraction pattern and the theoretically calculated pattern are in good agreement, which to a certain extent indicates that the crystal in this invention has the characteristic of high phase purity.
[0062] 3. First-principles calculations of the optical properties of Sb(SeO3)(HSeO3) crystals were performed using density functional theory (DFT) to obtain data on the crystal band gap and birefringence. The calculations used the Perdew-Burke-Ernzerhof (PBE) exchange-correlation functional under the generalized gradient approximation (GGA); all atoms employed mode-conserving pseudopotentials, and the plane wave energy cutoff was set to 850 eV; the Brillouin zone k-point grid sampling was set to 4×4×1, and the self-consistent field (SCF) energy convergence threshold was set to 1.0×10⁻⁶. -6 eV / atom, with other calculation parameters using the program's default values; the above calculations were performed in Materials Studio software using the CASTEP program. In the calculations, the valence electron configuration of each constituent atom is: Sb:5s 2 5p 3 Se:4s 2 4p 4 O:2s 2 2p 4 H:1s 1 .
[0063] The theoretical band gap of Sb(SeO3)(HSeO3) crystal was calculated to be 3.09 eV using the GGA-PBE method (see details). Figure 5 The ultraviolet absorption edge of the crystal was found to be 309 nm by ultraviolet-visible absorption spectroscopy. The experimental optical band gap was calculated to be 4.01 eV based on Eg = 1240 / λ (see details). Figure 7 Since GGA-PBE functionals typically underestimate the optical bandgap of materials, this calculation introduces a scissor operator for bandgap correction. The scissor operator offset is taken as the difference between the experimental optical bandgap and the theoretically calculated bandgap, i.e., 4.01 eV - 3.09 eV = 0.92 eV. Based on the dielectric function corrected by the scissor operator, the birefringence value of the crystal is accurately obtained, and the results are as follows. Figure 6 As shown.
[0064] from Figure 6 It can be seen that the crystal has a birefringence of 0.350 at a wavelength of 546nm, which is calculated by theory. This means that the crystal in this invention has a large birefringence efficiency, which is beneficial to accelerating the evolution of optoelectronic systems towards thinner and smaller designs.
[0065] 4. A Shimadzu UV2600 UV-Vis spectrophotometer, equipped with an ISR-2600 integrating sphere accessory, was used to analyze the UV-Vis diffuse reflectance spectrum of the test crystal powder in the 200-800 nm range, using barium sulfate (BaSO4) as a reference. The obtained raw data were fitted and transformed using the Kubelka-Munk function, and the apparent optical absorption edge energy of the crystal was calculated to provide basic data for subsequent optical property analysis; the test results are as follows. Figure 7 As shown.
[0066] from Figure 7 As can be seen from the data, the ultraviolet absorption edge of the crystal in this invention is 309 nm, indicating that the crystal in this invention has a large optical band gap and a wide near-ultraviolet / visible optical window.
[0067] In summary, the crystal in this invention has both a wide optical transmission range and strong polarization control capability, which accelerates the miniaturization process of optoelectronic systems.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A Sb(SeO3)(HSeO3) crystal form, characterized in that, The Sb(SeO3)(HSeO3) crystal is a crystal with a centrosymmetric structure; Using Cu-Kα radiation, the PXRD pattern of the Sb(SeO3)(HSeO3) crystal includes characteristic diffraction peaks at 2θ values of 6.06°, 12.10°, 25.52°, 27.42°, 31.92°, 36.92°, 43.22°, 44.84°, 54.32°, 54.78°, 56.52°, and 67.38°, with an error of ±0.2° for the 2θ values.
2. The Sb(SeO3)(HSeO3) crystal form according to claim 1, characterized in that, The crystal is an orthorhombic crystal system, the space group is Cmce, the cell parameters are: a(Å)=5.5791(3), b(Å)=6.9739(3), c(Å)=29.2383(17), α(°)=90°, β(°)=90°, γ(°)=90°, the cell volume is 1137.61(10), and the number of units in the formula is 8.
3. The Sb(SeO3)(HSeO3) crystal form according to claim 2, characterized in that, The crystal is formed as a single crystal, the space group is Cmce, the cell parameters are: a(Å)=5.5791(3), b(Å)=6.9739(3), c(Å)=29.2383(17), the cell volume is 1137.61(10), and the number of units in the formula is 8.
4. The Sb(SeO3)(HSeO3) crystal form according to claim 1, characterized in that, Using Cu-Kα radiation, the crystal exhibits the strongest characteristic diffraction peak at 2θ = 27.42° with a relative intensity of 100%, where the error in the 2θ value is ±0.20°.
5. The Sb(SeO3)(HSeO3) crystal form according to any one of claims 1 to 4, characterized in that, The crystal has a theoretically calculated birefringence of 0.350 at a wavelength of 546 nm, and an experimentally measured ultraviolet absorption edge of 309 nm.
6. A method for preparing Sb(SeO3)(HSeO3) crystals, characterized in that, include: After the reaction raw materials are dissolved in the solvent, an acidic liquid is added to adjust the pH of the reaction system to 0.5±0.
3. After static growth reaction, Sb(SeO3)(HSeO3) crystals are obtained. The reaction raw materials include soluble selenium-containing compounds and soluble antimony-containing compounds; The solvent includes deionized water.
7. The preparation method according to claim 6, characterized in that, The molar ratio of the soluble selenium-containing compound to the soluble antimony-containing compound is 1.8~2.2:1; The soluble selenium-containing compound includes selenium dioxide, and the soluble antimony-containing compound includes antimony trifluoride; The conditions for the static growth reaction include: reaction at room temperature for 7 to 15 days; The acidic liquid includes 80% sulfuric acid.
8. A polarizer, characterized in that, The polarizer is made of the Sb(SeO3)(HSeO3) crystal as described in any one of claims 1 to 5, or, It is made from Sb(SeO3)(HSeO3) crystals obtained by the preparation method described in claim 6 or 7.
9. A phase delay plate, characterized in that, The phase retarder is made of the Sb(SeO3)(HSeO3) crystal as described in any one of claims 1 to 5, or, It is made from Sb(SeO3)(HSeO3) crystals obtained by the preparation method described in claim 6 or 7.
10. A polarization beam splitter element, characterized in that, The polarization beam splitter element is made of the Sb(SeO3)(HSeO3) crystal as described in any one of claims 1 to 5, or, It is made from Sb(SeO3)(HSeO3) crystals obtained by the preparation method described in claim 6 or 7.